Constructing peace within war: Buddhism and International Humanitarian Law: Constructing peace within war: Buddhism and International Humanitarian Law - Cicuzza, Claudio (สหศาสตร์: วารสารสังคมศาสตร์และมนุษยศาสตร์, 2023)
During the last few years, we noticed a growing exchange of ideas between Buddhist scholars (from monastic and lay communities) and experts (activists, philosophers, scholars of international relations, etc.) working in the field of International Humanitarian Law (IHL). This fruitful dialogue seems particularly vital in Southeast Asia, where the dynamic office of the International Committee of the Red Cross (ICRC) in Bangkok, established in 1975, promotes meetings, academic conferences, joint publications, and regular sharing of ideas with Buddhist scholars. People from Asia and the West, from different Buddhist countries, and from various traditions and backgrounds, participate with fervent enthusiasm and competence in all these activities. After the successful international conference organized in Dambulla, Sri Lanka, in September 2019, the ICRC is now organizing – in collaboration with Chiang Mai University, Mahidol University, and Shan State Buddhist University – a second conference at Chiang Mai University, in December 2022, on the theme of “Reducing Suffering during Armed Conflict – The Interface between Buddhism and International Humanitarian Law”.[1] The International Humanitarian Law “is a set of rules that seek to limit the humanitarian consequences of armed conflicts. It is sometimes also referred to as the law of armed conflict or the law of war (jus in bello). The primary purpose of IHL is to restrict the means and methods of warfare that parties to a conflict may employ and to ensure the protection and humane treatment of persons who are not, or no longer, taking a direct part in the hostilities”.[2] I believe that the teachings of the Buddha are indispensable (and are becoming even more crucial nowadays) in reducing suffering and violence during any sort of war: the dialogue among Buddhist scholars and the International Committee of the Red Cross will soon bear fruits and positive results. [1] See the call for papers here: https://blogs.icrc.org/religion-humanitarianprinciples/call-for-papers-buddhism-ihl-chiang-mai/ [2] See International Humanitarian Law Answers to your Questions. (2015). Geneva: International Committee of the Red Cross, p. 17.